2005
DOI: 10.1111/j.1365-201x.2005.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of endurance and resistance exercise on muscle capillarization in the elderly: a review

Abstract: Part of the difficulty in determining the nature of these relationships has been the inconsistency in research conducted regarding age groups and controlling for past and present activity patterns. Further difficulties comparing across studies arise due to the variety of methods and parameters used to sample and analyse muscle tissue. Standardizing methodology will allow future research to yield more consistent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 45 publications
(138 reference statements)
2
43
1
1
Order By: Relevance
“…Harris also reported that aerobic exercise can result in positive structural and functional changes with respect to skeletal muscle capillarization in elderly subjects [64]. Similarly, an eight-week aerobic exercise intervention increased capillary contacts, capillary-to-fiber ratio, and capillary density in both healthy young and elderly subjects, but did not change any of the parameters regarding muscle fiber size [67].…”
Section: Morphological Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Harris also reported that aerobic exercise can result in positive structural and functional changes with respect to skeletal muscle capillarization in elderly subjects [64]. Similarly, an eight-week aerobic exercise intervention increased capillary contacts, capillary-to-fiber ratio, and capillary density in both healthy young and elderly subjects, but did not change any of the parameters regarding muscle fiber size [67].…”
Section: Morphological Outcomesmentioning
confidence: 99%
“…One systematic review reported conflicting evidence regarding the effects of resistance training on muscle capillarization in the elderly subjects [64]. An increase in muscle fiber size was accompanied by significant increases in capillary contacts per fiber, capillary to fiber ratio and capillary to fiber perimeter exchange index, but the growth of capillaries was proportional to fiber growth, resulting in no change to sharing factor, capillary density or capillary contacts per fiber area [64][65][66].…”
Section: Morphological Outcomesmentioning
confidence: 99%
“…Despite conflicting results, some studies shown minimal reduction in the number of capillaries of skeletal muscles during age advancing 1 . Muscle capillarization must represent the potential to exchange gases, fuel and metabolites during exercise 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite conflicting results, some studies showed minimal reduction in the number of capillaries from muscles of elderly compared to young 1 . Even so, the amount of work proposing to analyze the aging effect on vascularity of different skeletal muscle types is small.…”
Section: Introductionmentioning
confidence: 99%
“…This metabolic difference fades with menopausal hormone changes (Isacco et al 2012), possibly making postmenopausal women prone to fat gain. Low activity combined with low estrogen levels after menopause may also limit the body's ability to build cardiovascular and muscular adaptations to exercise (Grounds 1998;Grounds 2002;Harris 2005), potentially blunting the health benefits of exercise interventions in sedentary postmenopausal women. These factors suggest that postmenopausal women are more susceptible to metabolic diseases regardless of exercise levels.…”
Section: Evolutionary Expectations For Postmenopausal Healthmentioning
confidence: 99%